The Arteriovenous Loop: Engineering of Axially Vascularized Tissue - Weigand, Annika; Horch, Raymund E.; Boos, Anja; Beier, Justus P.; Arkudas, Andreas (European Surgical Research, 2018)
BACKGROUND: Most of the current treatment options for large-scale tissue defects represent a serious burden for the patients, are often not satisfying, and can be associated with significant side effects. Although major achievements have already been made in the field of tissue engineering, the clinical translation in case of extensive tissue defects is only in its early stages. The main challenge and reason for the failure of most tissue engineering approaches is the missing vascularization within large-scale transplants. SUMMARY: The arteriovenous (AV) loop model is an in vivo tissue engineering strategy for generating axially vascularized tissues using the own body as a bioreactor. A superficial artery and vein are anastomosed to create an AV loop. This AV loop is placed into an implantation chamber for prevascularization of the chamber inside, e.g., a scaffold, cells, and growth factors. Subsequently, the generated tissue can be transplanted with its vascular axis into the defect site and anastomosed to the local vasculature. Since the blood supply of the growing tissue is based on the AV loop, it will be immediately perfused with blood in the recipient site leading to optimal healing conditions even in the case of poorly vascularized defects. Using this tissue engineering approach, a multitude of different axially vascularized tissues could be generated, such as bone, skeletal or heart muscle, or lymphatic tissues. Upscaling from the small animal AV loop model into a preclinical large animal model could pave the way for the first successful attempt in clinical application. Key Messages: The AV loop model is a powerful tool for the generation of different axially vascularized replacement tissues. Due to minimal donor site morbidity and the possibility to generate patient-specific tissues variable in type and size, this in vivo tissue engineering approach can be considered as a promising alternative therapy to current treatment options of large-scale defects.
EVALuna2:211483